CALITATEA ŞI PERFORMANŢA RESURSELOR UMANE - OBIECTIVE ALE EDUCAŢIEI PROSPECTIVE ÎN CADRUL UNIVERSITAR - USM ADMIN (Moldova State University, 2010)
The progressive development of the society advertises the need and importance of interventions in the university which has as purpose preparing human resources. In this context, the issues of quality assurance are specified by the fact that the education is responsible for sustainable development which is determined by the quality of the education. The answer to these requirements can provide the prospective education - the methodological principle of the education, aimed to participate at sustainable development of society in terms of higher education, by comparing them to current and future requirements of society, by targeting of the school to a new way of education.